Economic-social interaction in China - Assar Lindbeck (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes economic-social interaction in China in connection with the country's change of economic system. I define an economic system in terms of a multidimensional vector of broad institutional characteristics, and I emphasize that important features of the social development are closely related to specific changes in these various dimensions. I classify China's options for future social improvements into three broad categories: policies that improve the stability and distribution of factor income; government-created wedges between factor income and disposable income; and improvements in the quantity, quality and distribution of human services, such as education and health care.
Keywords: P2; H00; I00; 330; China; economic transition; typology of economic systems; social reforms; Systemtransformation; Wirtschaftsreform; Sozialer Wandel; Sozialpolitik; Sozialer Dienst; China